BANANA FLOUR PROCESSING AT THE VILLAGE WOWOLI TOARI DISTRICT OF KOLAKA - Nursalam Nursalam; Yuli Purbaningsih (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2016)
Processing business of banana flour is a business that is the utilization of agricultural products combined with local knowledge will result in a business that is not only interested in the business, but also will increase the added value of agricultural products and the main thing is to increase the value of bananas from economical low into a product which has a high economic value can increase the added value of farmers in terms of product diversification. The business group banana flour in the village Wowoli Toari District of Kolaka comprised of mothers of farm households collected in Welasih business groups and business groups of Sido Maju. Both partners develop business plantain flour and banana farmers as provider of raw materials. Raw materials used banana banana flour that has been processed through drying. Method of activities carried out in both partners is the application and practice of using a pressing machine, pressing the practice reduces packaging for air content in aluminum foil and practices as well as the sale process of drying banana banana flour heating process. Based on the results of the training activities of banana flour processing as a result of the diversification of the banana plant can be concluded that, their knowledge of cultivation and post-harvest handling and processing technologies banana flour in an effort to increase farmers' income. Through this training, the production of abundant banana plants can be overcome because farmers can cultivate their own, in an attempt diversification of food as well as value-added income of farmers. The results of the analysis of flour processing enterprises banana production unity earn Rp 63.100 value added raw materials Rp 2.931 union production.